Fabrication and analysis of mechanical properties of PVC/Glass fiber/graphene nano composite pipes. (4th November 2020) - Shanmugasundar, G; Vanitha, M; Babu, L Ganesh; Suresh, P; Mathiyalagan, P; Krishnan, G Sai; Makos, Mebratu
Abstract: The aim of this work is to examine the conventional moulding method for manufacturing the PVC/Glass fiber/graphene nano composites. Uniform graphene dispersion is observed with the matrix for better bonding. The Mechanical properties of the manufactured nano composites have been done in this work. Three important standard tests were evaluated for the performance of Nano-Composites developed. The composites were developed as flat specimen for pipe applications. The three standards test which includes axial tension, compression and transverse compression is studied. The graphene nano composites were varied 0.5%, 1%, 1.5% and 2 percentages. Based on the results it can be concluded that the increase in the percentages of graphene made a uniform dispersion, which leads to increase in the compressive strength of the Nanocomposite. Increase in the axial compressive strength and stiffness was observed and the increase in the trend value is mainly observed in 1.5 wt% and 2 wt% respectively. The Graphene dispersion and fractured surface morphology of nano composites were examined using scanning electronic microscopy (SEM).It can also be used as an alternative for metal pipes in industries.